Características da carcaça e da carne de cordeiros alimentados com palma forrageira em substituição ao farelo de trigo - ABREU, Karen Santos Félix de (2014)
The effect of replacement of wheat bran by Spineless cactus and urea (0, 33, 66 and 100 %) in the diet of lambs on objective and subjective measures; tissue composition and chemical composition of meat we studied. For this, 36 lambs were used averaging four months of age with and initial body weight of 19.5 ± 1,6 kg were distributed in a randomized block design with four treatments and nine replicates and slaughtered after 70 days of confinement. The carcass were cooled to 4° C for 24 hours, immediately after slaughter, subsequently, the morphometric measurements and subjective evaluations of the carcass were measured. And were used the left leg of each animal to tissue composition and, after dissection; there was the chemical composition of meat using the semimembranosus muscle. No significant influences on the conformation and the carcasses (mean score = 3.04 and 2.78) were observed, but the perirenal fat showed a quadratic effect, with maximum subjective score of 2.46 to 47.37% replacement. The variables of leg tissue composition were influenced not by replacing, with average values of 1522.86g of muscle and 69.90% of revenue from edible tissue. Not does the composition of the meat suffered influences of substitution, with average values of 75.19%, 1.18%, 18.29% and 2.87% for moisture, ash, crude protein (CP) and ether extract (EE), respectively. The spineless cactus can fully replace wheat bran in the diet of lambs, as showed no decrease in quantitative carcass traits.